Recurrent staphylococcal abscess in an adolescent with hyperimmunoglobulin E syndrome: A rare presentation - Ahmad, Najeeb; Bhakat, Rahul; Chacham, Swathi; Singh, Avinish; Mandal, Debdip; Naseeruddin, Shaik; Bhat, Nowneet Kumar; Naithani, Manisha (Indian Journal of Child Health, 2020)
Hyperimmunoglobulin E syndrome (HIES) more commonly referred to as Job’s syndrome, is an infrequent primary immunodeficiency disorder. It can be inherited either by autosomal dominant or recessive mode with each one having distinct varied clinical presentation. The distinguishing clinical features include recurrent infections, dermatitis, and elevated serum immunoglobulin E (IgE) levels. We report a case of an adolescent female who presented with recurrent staphylococcal infection with axillary lymphadenitis, positive family history, and abnormal facial features mainly broad forehead, facial asymmetry, and peripheral blood eosinophilia with significantly high serum IgE levels, suggestive of autosomal dominant HIES.